2021
DOI: 10.1186/s13256-021-02868-5
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-free anesthesia—dexmedetomidine as adjuvant in erector spinae plane block: a case series

Abstract: Background Laparoscopic pain is related to the stretching of the peritoneum and peritoneal irritation caused by insufflation of the parietal peritoneum with carbon dioxide. In 2017, erector spinae plane block (ESPB) was described for management of postoperative pain following open and laparoscopic abdominal surgery. The use of multimodal anesthesia reduces both intraoperative and postoperative opioid use and improves analgesia. The addition of dexmedetomidine to the anesthetic mixture significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“… 10 There have been multiple studies claiming increased effectiveness of use of dexmedetomidine and this has been consolidated in a meta-analysis examining the effectiveness of dexmedetomidine as a peripheral nerve block adjuvant. 11 , 12 However, whether interfasical dexmedetomidine prolongs the duration of single-injection ESPB and reduces postoperative opioid consumption after curative-intent open thoracotomy remains uncertain. Therefore, this prospective, randomized, double-blinded, controlled clinical study was performed to investigate whether adding dexmedetomidine to ropivacaine could prolong the duration of single-injection ESPB and reduce postoperative opioid consumption for open thoracotomy.…”
mentioning
confidence: 99%
“… 10 There have been multiple studies claiming increased effectiveness of use of dexmedetomidine and this has been consolidated in a meta-analysis examining the effectiveness of dexmedetomidine as a peripheral nerve block adjuvant. 11 , 12 However, whether interfasical dexmedetomidine prolongs the duration of single-injection ESPB and reduces postoperative opioid consumption after curative-intent open thoracotomy remains uncertain. Therefore, this prospective, randomized, double-blinded, controlled clinical study was performed to investigate whether adding dexmedetomidine to ropivacaine could prolong the duration of single-injection ESPB and reduce postoperative opioid consumption for open thoracotomy.…”
mentioning
confidence: 99%
“…Perineural administration of local anesthetic adjuvants, such as dexamethasone, fentanyl, dexmedetomidine, clonidine, and epinephrine, has been used to extend the duration of analgesia after PNB. 11,12 The benefits and drawbacks of using these adjuvants have been studied in several randomized controlled trials and meta-analyses. 11,13 In addition, the concept of "multimodal perineural analgesia (MMPNA)" has been introduced in recent animal safety and clinical observational studies.…”
Section: Resultsmentioning
confidence: 99%
“…A significant issue associated with single-shot peripheral nerve blocks (PNBs) is related to the limited duration of action of the presently available local anesthetics. Perineural administration of local anesthetic adjuvants, such as dexamethasone, fentanyl, dexmedetomidine, clonidine, and epinephrine, has been used to extend the duration of analgesia after PNB 11,12 . The benefits and drawbacks of using these adjuvants have been studied in several randomized controlled trials and meta-analyses 11,13 .…”
mentioning
confidence: 99%
“…It has been shown that the use of multimodal anesthesia by improving analgesia reduces the use of intraoperative and postoperative opioids (3). A growing body of evidence supports the adjuvant use of dexmedetomidine in locoregional anesthesia significantly prolongs the analgesia and potentiates the effect, without clinically significant side effects (4,5).…”
Section: Introductionmentioning
confidence: 99%